Studying rod photoreceptor development in zebrafish - Morris, A.C. (2005)
The zebrafish has rapidly become a favored model vertebrate organism, well suited for studies of developmental processes using large-scale genetic screens. In particular, zebrafish morphological and behavioral genetic screens have led to the identification of genes important for development of the retinal photoreceptors. This may help clarify the genetic mechanisms underlying human photoreceptor development and dysfunction in retinal diseases. In this review, we present the advantages of zebrafish as a vertebrate model organism, summarize retinal and photoreceptor cell development in zebrafish, with emphasis on the rod photoreceptors, and describe zebrafish visual behaviors that can be used for genetic screens. We then describe some of the photoreceptor cell mutants that have been isolated in morphological and behavioral screens and discuss the limitations of current screening methods for uncovering mutations that specifically affect rod function. Finally, we present some alternative strategies to target the rod developmental pathway in zebrafish.